How did the youth labour market situation evolve between 2012 and 2013? Second release of the KOF Youth Labour Market Index - Filippo Pusterla (ETH Zurich, KOF Swiss Economic Institute, 2015)
The KOF Youth Labour Market Index (KOF YLMI) describes the youth situation on the labour market with a multidimensional approach. Not only labour market status matter, but also working conditions, provided education and the ease of entry into the labour market is considered. Switzerland achieved in 2013 an index score of 5.66. That is a slight increase compared to the last publication of the KOF YLMI. The EU28 average was 4.60. However, while Switzerland still has the highest KOF YLMI, the labour market situation in Denmark, Germany and Austria has improved more than in Switzerland, thereby reducing the lead of Switzerland. Unfortunately, the change in the KOF YLMI shows that the youth labour market situation has deteriorated further in Cyprus, Greece, Portugal, Italy and Spain.
Keywords: 330